Optimization of insect cell based protein production processes - online monitoring, expression systems, scale-up - Druzinec, Damir; Salzig, Denise; Brix, Alexander; Kraume, Matthias; Vilcinskas, Andreas; Kollewe, Christian; Czermak, Peter (Springer, 2014)
Due to the increasing use of insect cell based expression systems in research and industrial recombinant protein production, the development of efficient and reproducible production processes remains a challenging task. In this context, the application of online monitoring techniques is intended to ensure high and reproducible product qualities already during the early phases of process development. In the following chapter, the most common transient and stable insect cell based expression systems are briefly introduced. Novel applications of insect cell based expression systems for the production of insect derived antimicrobial peptides/proteins (AMPs) are discussed using the example of G. mellonella derived gloverin. Suitable in situ sensor techniques for insect cell culture monitoring in disposable and common bioreactor systems are outlined with respect to optical and capacitive sensor concepts. Since scale-up of production processes is one of the most critical steps in process development, a conclusive overview is given about scale up aspects for industrial insect cell culture processes.
Keywords: BEVS; Drosophila S2; In situ monitoring; Gloverin; FBRM; Scale up